(untitled) (Baghdad Science Journal, 2010)
Five serological methods for detection of Brucella were compaired in this study, Four of the methods are commonely used in the detections:- 1-Rose-Bengal: as primary screening test which depends on detecting antibodies in the blood serum. 2-IFAT: which detects IgG and IgM antibodies in the serum. 3-ELISA test: which detects IgG antibodies in the serum. 4-2ME test: which detects IgG antibodies The fifth methods. It was developed by a reasercher in one of the health centers in Baghdad. It was given the name of spot Immune Assay (SIA). Results declares that among (100) samples of patients blood, 76, 49, 49, 37, and 28. samples were positive to Rose Bengal, ELISA, SIA, 2ME and IFAT tests, respectively. When efficiency, sensitivity and specificity of the serological methods were compaired, the Following results were obtained: a) ELISA and SIA were superiors among the other confirming methods (2ME and IFAT) in detecting the highest cases (49 cases); 46 of them were from the (76) cases positive to Rose Bengal The confirmatory test 2ME was not efficient in detecting low concentrations of IgG antibodies when less than half (37) of the total positive cases (76) were detected by this test. b) IFAT test was the least efficient confirmatory test among all other test. c) As a new confirmatory test, SIA proved to be an efficient and serological test for Brucella detection in comparison with other tests. It is an easy to use test, rapid and could be performed without need to the expensive equipment .